A study on the image of public libraries as perceived by the local government officials and civil servants in the municipality of Rodriguez, Rizal - Evangelista, Pearly Ann P.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
As mandated by Republic act No. 7743, “An Act Providing for the Establishment of Congressional, City and Municipal Libraries and Barangay Reading Centers Throughout the Philippines, Appropriating the Necessary Funds Therefor and for Other Purposes,” the local government of Rodriguez, Rizal is required to put up a public library and barangay reading centers in their respective areas.

The Municipality of Rodriguez, Rizal has existing municipal library. However, to this day, most barangays in the municipality do not have a barangay reading center.

The study aims to provide information and to have a better understanding of the politicians’ perspectives on the roles and development of public libraries in the Philippines.

Through the survey, this study determined the awareness, knowledge, and understanding of local government officials and civil servants on the importance of public libraries, and their responsiveness toward development and establishment of public libraries in the municipality.
Thesis
Keywords: Public libraries -- Philippines -- Luzon